the Education Reform in the Scientific Hawzas (Shia Religious Centers) of Najaf during the Royal Period and the Conflict of Originality and Renewal (Journal of the College of Basic Education, 2019)
This paper tackles the "Education Reform in the Scientific Hawzas (Shia Religious Centers) of Najaf during the Royal Period and the Conflict of Originality and Renewal". The importance of the paper stems from the fact that it deals with one of the oldest religious schools in the world. It consists of three topics. The first one is about the importance of reforming education in the Hawzaz. The second one is about the reform project of Sheikh Mohammed Al-Hussein Al-Kashif. The third topic is about the project of the Publishing Forum association. The paper ends with some conclusions, the most important of which is that the stage of foundation the modern Iraqi state has produced urgent requirements for reforming education in accordance with the spirit of the time. The reform caused a conflict between conservatives and reformists, resulting in intellectual openness and literary wealth in Najaf's conservative milieu. The reform projects have not been able to achieve their objectives due to the strength of the conservative trend on one hand, and not to touch these projects to offset the compatibility between originality and innovation without prejudice to the privacy of the scientific estates on the other hand.